Enneagram: An Illustrative Exploration - Thomas, Jordan (East Carolina University, 2016)
“Enneagram: An Illustrative Exploration” is a collection of work created during my last two years as a BFA Candidate in Studio Art and Illustration. The bulk of the work is based around body adornment and tattooing and how body modification is a means by which we outwardly express our inner narrative.
Keywords: tattoo, illustration